2023
DOI: 10.3390/molecules28166063
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Radix Astragali from Different Growth Patterns, Origins, Species, and Growth Years by an H1-NMR Spectrogram of Polysaccharide Analysis Combined with Chemical Pattern Recognition and Determination of Its Polysaccharide Content and Immunological Activity

Abstract: The fraud phenomenon is currently widespread in the traditional Chinese medicine Radix Astragali (RA) market, especially where high-quality RA is substituted with low-quality RA. In this case, focused on polysaccharides from RA, the classification models were established for discrimination of RA from different growth patterns, origins, species, and growth years. 1H Nuclear Magnetic Resonance (H1-NMR) was used to establish the spectroscopy of polysaccharides from RA, which were used to distinguish RA via chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…The model was further validated by random permutation testing for 200 iterations (Figure 6b), and the results showed that R 2 = (0.0,0.391), Q 2 = (0.0,−0.0923). As the Y ‐intercept of the Q 2 fitting line was −1.08 (less than 0), and the rightmost point had higher Q 2 and R 2 values than the left, it is shown that the constructed model does not overfit and can be used for data analysis of differences in sample quality components among different developmental stages (Guo et al., 2023).…”
Section: Resultsmentioning
confidence: 99%
“…The model was further validated by random permutation testing for 200 iterations (Figure 6b), and the results showed that R 2 = (0.0,0.391), Q 2 = (0.0,−0.0923). As the Y ‐intercept of the Q 2 fitting line was −1.08 (less than 0), and the rightmost point had higher Q 2 and R 2 values than the left, it is shown that the constructed model does not overfit and can be used for data analysis of differences in sample quality components among different developmental stages (Guo et al., 2023).…”
Section: Resultsmentioning
confidence: 99%